Efisiensi dan kesesuaian kapasitas sistem Plumbing pada bangunan tinggi berdasarkan beban air hunian dan fasilitas pendukung - Zufri Hasrudy Siregar; Arif Fadillah Nasution; Refiza Refiza (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2026)
The rapid growth of vertical housing in urban areas increases the complexity of plumbing system management, as the system must ensure reliable water supply, energy efficiency, and service performance for a large number of occupants simultaneously. However, most plumbing system designs still rely on conventional assumptions such as 120 L/person/day water demand and 3 days of storage capacity, which often do not represent the actual consumption patterns of modern buildings. This study aims to evaluate the efficiency and capacity suitability of plumbing systems in high-rise residential buildings based on occupant water demand and supporting facilities. The novelty of this research lies in the development of an integrated Key Performance Indicators (KPI) framework consisting of four main dimensions: water efficiency, pump energy efficiency, hydraulic service quality, and user comfort. The research method involves numerical analysis of water demand based on the number of occupants, evaluation of Ground Water Tank (GWT) and Sewage Treatment Plant (STP) capacities, and system performance assessment using quantitative KPI metrics. The results demonstrate that the proposed evaluation model effectively identifies operational efficiency levels and provides an analytical basis for optimizing plumbing capacity and sustainable building utility management.